Epidemiological profile of leprosy in the municipality of Divinópolis, Minas Gerais - Fernanda Moura Lanza; Daniel Nogueira Cortez; Tarcísio Laerte Gontijo; Janaína de São José Rodrigues (Universidade Federal de Santa Maria, 2012)
Objective: to analyze the epidemiological profile of leprosy in Divinópolis/MG. Method: this is cross-sectional and descriptive study. Data were collected in the Information System for Notifiable Diseases, for the period 2001 to 2010. Results: during the period under study has reported 124 cases of leprosy living in the city, mostly in individuals over 15 years with a predominance of multibacillary and zero degree of disability at diagnosis. The hidden prevalence of leprosy in the period 2006 to 2010 was 12 cases. Conclusion: we conclude that the current organization of health services contributes to late diagnosis and highlights the need to integrate primary health care in the conduct of actions to control leprosy